2022
DOI: 10.1186/s12958-022-01015-z
|View full text |Cite
|
Sign up to set email alerts
|

Why Turner patients with 45, X monosomy should not be excluded from fertility preservation services

Abstract: In this case report, we highlight the practical dilemma, i.e. to perform ovarian tissue cryopreservation surgery in a 45, X Turner Syndrome patient or not, by reporting on the presence of follicles in a 13-year-old female diagnosed with 45, X monosomy and an unmeasurable anti-müllerian hormone serum level. We compare our results with previous research, highlight the challenges we faced in this case and provide recommendations for daily practice. Hereby, we demonstrate that excluding certain subgroups of Turner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Recently, Schleedoorn et al. highlighted the practical dilemma (i.e., to perform OTC surgery in a 45, X TS patient or not) by reporting on the presence of follicles in a 13-year-old female diagnosed with 45, X monosomy and an unmeasurable AMH ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Schleedoorn et al. highlighted the practical dilemma (i.e., to perform OTC surgery in a 45, X TS patient or not) by reporting on the presence of follicles in a 13-year-old female diagnosed with 45, X monosomy and an unmeasurable AMH ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oocyte cryopreservation (also known as egg freezing) attempts to obtain eggs from the ovary following artificial stimulation with exogenous hormones and allows storage by freezing these eggs until they are required for reproduction. A literature review studied 18 cases of mosaic TS (17 cases without amenorrhoea; one case not reported) with successful oocyte cryopreservation 23 . Another study followed seven women with TS undergoing oocyte cryopreservation after ovarian hyperstimulation.…”
Section: Fertility Preservationmentioning
confidence: 99%
“…Infertility is the leading source of anxiety and depression for women with a diagnosis of TS. [22][23][24] A late diagnosis of TS (i.e., after 13 years) is also a risk factor for depression 25 perhaps due to the lost opportunity of earlier fertility or utilisation of fertility preserving techniques. The recent international TS guidelines 3 recommend that women be counselled regarding the reducing rates of spontaneous conception with age and that fertility treatment should be offered to young women.…”
Section: Fertility Preservationmentioning
confidence: 99%
“…Interviews of both parents of young girls and adolescents with Turner syndrome and healthcare providers have revealed that fertility counselling is difficult. Discussions of preservation techniques can raise high hopes for the future, and counselling of realistic expectations can be challenging for providers [62 ] Given both the heterogeneity of fertility potential in women with Turner syndrome and success rates of assisted reproductive technologies (ARTs), guidelines for procreative management are largely based on expert opinion. For those with spontaneous, regular menses and minimal other clinical manifestations of Turner syndrome, early attempts at unassisted conception are encouraged due to the inability to predict timing of follicle loss.…”
Section: Fertility Counselling For Women and Familiesmentioning
confidence: 99%
“…For those with spontaneous, regular menses and minimal other clinical manifestations of Turner syndrome, early attempts at unassisted conception are encouraged due to the inability to predict timing of follicle loss. For adolescents and young women with spontaneous puberty, oocyte cryopreservation has been recommended in those with regular cycles, near-normal levels of ovarian reserve, age 12 or older, and perhaps only with mosaic karyotypes [20,33 ▪▪ ], yet there are case reports that contradict this guidance [27,55 ▪▪ ,63 ▪ ]. For counselling parents of prepubertal girls considering OTC, experts suggest evaluation first with ultrasound to confirm the presence of at least one visualized ovary and subsequent assessment of FSH [61].…”
Section: Recommendations For Fertility Management In Women With Turne...mentioning
confidence: 99%